Anatomical characterization of oblique popliteal ligament and its clinical significance on knee joint stability - Mamatha Hosapatna; Shreya Saha; Muralimanju B V; Soumyalatha Naveen; Rohini Punja (Translational Research in Anatomy)
Background: The oblique popliteal ligament (OPL) plays a crucial role in knee stability, yet its anatomical variations are not fully understood. This study aimed to provide a comprehensive morphometric and morphological analysis of the OPL in the South Indian population. Methods: Twenty cadaveric knee specimens were dissected and examined. The length and width of the OPL were measured using digital calipers. Morphological characteristics, including shape and attachment patterns, were observed and classified. Results: The mean length of the OPL was 28.9 ± 3.7 mm, with a width of 17.5 ± 4.3 mm at the origin and 18.3 ± 4.4 mm at the midpoint. Three main types of OPL were identified: Type 1 (45 %) with an accessory upper band, Type 2 (30 %) with a broad medial attachment, and Type 4 (25 %) with a fan-like appearance. Five shape variations were observed: band shape (30 %), trident shape (25 %), complex shape (20 %), Z-shape (15 %), and Y-shape (10 %). Conclusion: This study reveals significant variability in OPL morphology and dimensions. These findings have important implications for understanding knee biomechanics, improving surgical techniques, and enhancing the interpretation of imaging studies of the posterior knee.